Carl Gustav Jung, Teori Transformasi dan Relevansinya pada Organisasi Birokrasi - Ambar Widaningrum (Buletin Psikologi, 2006)
One of primary issues of organization theory debate arises from questions about the basic unit analysis from which the reality of organization is best derived or understood. The functionalist orientation takes as its points from the larger collective level of  reality, that is, the encompassing system is the basic unit of analysis. The interpretivists see individual interaction as the basic unit from which an understanding of the larger context can be obtained. The two perspectives have no link between the individual and the collective, and the interface between them is un‐addressed. The notion of ʺsocialʺ is aborted. A transformational theory, which takes the Jung model (a psychological sociology) as a point of origin has the potential for this integrative perspective. This theory encompasses both the individual and the social and the nature of their interrelatedness.